Novel liquid sample transmission electron microscopic observation method based on nanometer quartz glass tube

By using nano-quartz glass tubes and vacuum evaporation method to prepare liquid storage units, the problems of complicated and high-cost preparation of liquid storage units in the existing technology are solved, and low-cost, fast and easy preparation of liquid storage units with high resolution is achieved. and liquid mixing function.

CN119334979APending Publication Date: 2025-01-21PEKING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310879996.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the existing in-situ liquid transmission electron microscopy technology, the preparation process of the liquid storage unit is complex, the equipment requirements are high, and the cost is expensive. The graphene liquid unit has shortcomings in the positioning, morphology and volume control of the liquid unit.

Method used

The nano -quartz glass tube is used as a liquid storage unit, and the nano -level quartz glass tube is prepared through the program -controlled laser tube method, combined with the vacuum steaming method on the surface of the glass tube steamed carbon plating layer, to prepare low cost, fast and simple, compatible standard samples The universal liquid unit of the rod.

Benefits of technology

It realizes the low-cost, quick and easy preparation of liquid storage units, has the ability to observe the dynamic process of substances in the liquid environment in real time, has good resolution, and has the function of liquid mixing, which significantly reduces the preparation and use costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004344185650000051
    Figure BDA0004344185650000051
  • Figure BDA0004344185650000071
    Figure BDA0004344185650000071
  • Figure HDA0004344185680000011
    Figure HDA0004344185680000011
Patent Text Reader

Abstract

The invention discloses a liquid sample transmission electron microscopic observation method based on a nanometer quartz glass tube. The method comprises the following steps: preparing a nano quartz glass tube by a laser program control drawing method, injecting a liquid sample into the nano quartz glass tube, cutting the tip part of the nano quartz glass tube in the presence of a sealing reagent, transferring and loading the tip part on a universal carrying net coated with a carbon film by using a capillary tube in an auxiliary manner, and then transmission electron microscopic observation can be carried out. Compared with the prior art, the method has the advantages of low cost, simple preparation process and the like, has a good resolution ratio and fluid mixing function, and has a wide application prospect in the field of transmission electron microimaging of liquid samples.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quartz glass tube liquid unit preparation and packaging and liquid environment transmission electron microscopy, and in particular relates to a liquid sample transmission electron microscopy observation method based on a nano-quartz glass tube. Background Art

[0002] In situ liquid phase TEM (LP-TEM) is a technique developed in the last decade to observe the dynamic behavior of liquid samples in situ and at high resolution. The key is to design a liquid storage unit to achieve a vacuum degree of 10° (~10°) in the sample chamber of the TEM. -5 Transmission electron microscopy observation of liquid samples under the condition of 1.477 Pa (Pa). This technology has been widely used to study the nucleation, growth, aggregation process of nanomaterials in liquid environment, as well as the dynamic behavior of microscopic conformational transition and interaction of biomacromolecules. At present, the liquid storage units used for in-situ liquid transmission electron microscopy can be divided into two categories: one is the in-situ liquid chip based on silicon nitride thin film material; the other is the liquid unit based on graphene encapsulation. Among them, the in-situ liquid chip based on silicon nitride thin film material is usually a composite structure of silicon crystal prepared by anisotropic wet etching technology as a liquid sample tank and silicon nitride film as an observation window. The preparation process is relatively complex and the equipment requirements are high. The silicon nitride-based liquid chip has the function of liquid mixing but needs to be matched with a special sample rod and flow control system, which is expensive. The graphene-based liquid unit benefits from the atomic thickness and good conductivity of graphene. It has ultra-high resolution and low sample damage rate, and is compatible with standard sample rods. However, due to the randomness of the generation and sample encapsulation process of single-layer (or multi-layer) graphene liquid units, there are shortcomings in liquid unit positioning, liquid unit morphology, and liquid volume control. Therefore, developing a liquid storage unit with low cost, efficient and simple preparation, good resolution and liquid mixing function is a key technical problem that needs to be urgently solved in the field of in-situ liquid electron microscopy technology. Summary of the invention

[0003] One object of the present invention is to provide a novel universal liquid unit preparation method based on nano-quartz glass tubes, which is applied to liquid phase transmission electron microscopy to observe the dynamic behavior of various nano-scale species changes. The present invention has the characteristics of low cost, rapidity and simplicity, and compatibility with standard sample rods, and has the ability to observe the dynamic process of substances in a liquid environment in real time. It can realize in-situ chemical reactions, nanomaterials, soft matter (vesicles, micelles, etc.), in-situ nucleation and growth processes of macromolecules and nanomaterials, and observation of nanodroplets and fluids.

[0004] The method for preparing a universal liquid unit based on a nano-quartz glass tube provided by the present invention comprises the following steps:

[0005] 1) preparing a quartz glass tube with a nanoscale tip;

[0006] 2) pouring the liquid sample to be observed into the quartz glass tube with the nanoscale tip, and letting it stand to fill the tip;

[0007] 3) cutting the tip of the nano-quartz glass tube in the presence of a sealing reagent, transferring and loading it onto a universal grid;

[0008] 4) About 1 μL of a fixing liquid (a 1,2-dichloroethane solution with a mass fraction of 1% polyvinyl formal) was added dropwise to the tail of the sample, and after the fixing liquid was completely solidified, a universal liquid unit based on a nano-quartz glass tube was obtained.

[0009] Furthermore, the method further comprises the following step: vacuum evaporating a carbon layer with a thickness of 5-15 nm on the surface of the glass tube of the universal liquid unit based on the nano-quartz glass tube, wherein the thickness of the carbon layer is preferably 10 nm.

[0010] In step 1) of the above method, the nano-quartz glass tube includes two types: single-channel and double-channel.

[0011] In step 1) of the above method, the length of the nanoscale tip segment (ie, the liquid storage unit) of the quartz glass tube is 0.5 mm to 2.5 mm, preferably 2 mm.

[0012] In step 1) of the above method, the radius of the tip of the nanoscale quartz capillary is 10-100 nm, preferably 50 nm or less, and more preferably 10 nm or less.

[0013] In step 1) of the above method, a quartz glass tube with a nanoscale tip is prepared by a program-controlled laser drawing method.

[0014] In step 2) of the above method, the original environment of the sample is liquid, including precursor solution, hard material (such as solution for synthesizing nanoparticles, nanoparticles, etc.), soft matter (such as vesicles, micelles, etc.), etc.

[0015] In step 2) of the above method, the standing time may be five minutes.

[0016] The specific method of step 3) of the above method can be: use micro scissors covered with high vacuum silicone grease to cut the nanometer-scale tip part of the quartz glass tube and seal its rear end in situ, and under microscope observation, use a capillary (micrometer-scale glass capillary can be used) to assist in transferring the high vacuum silicone grease and the tip of the quartz glass tube with the tail embedded therein to the universal carrier grid, ensuring that the needle tip and the carrier grid are basically in the same horizontal plane.

[0017] When the nano-quartz glass tube is a double-channel type, it is also necessary to adjust the middle partition of the double-channel nano-glass tube to be perpendicular to the grid plane.

[0018] In step 3) of the above method, the surface of the universal grid used is coated with a carbon film and the mesh size is 75-200 mesh, preferably 100 mesh. The size specification of the grid coated with the carbon film can be round with a diameter of 3 mm.

[0019] In step 4) of the above method, the purpose of adding the fixing liquid is to fix the liquid storage unit on the carrier grid.

[0020] The fixing liquid can be specifically a 1,2-dichloroethane solution containing 1% polyvinyl formal by mass. The amount of the fixing liquid used is about 1 μL.

[0021] When the nano-quartz glass tube is a dual-channel one, the liquid storage unit with a liquid mixing function based on the dual-channel nano-quartz glass tube comprises the following steps:

[0022] A double-channel quartz glass tube with a nanoscale tip (radius up to 20nm) was prepared by program-controlled laser drawing. The two liquid samples to be mixed were injected into the two channels of the double-channel capillary respectively, and left to stand for five minutes to fill the tip; the tip part (about 2mm) of the quartz glass tube was cut with micro scissors covered with high vacuum silicone grease and its rear end was sealed in situ, and then the high vacuum silicone grease and the quartz glass tube tip embedded in the tail were transferred to a universal grid covered with a carbon film with the aid of a capillary, and the middle partition of the double-channel nanoglass tube was adjusted to be perpendicular to the grid plane. Finally, about 1μL of the fixing solution (1,2-dichloroethane solution with a mass fraction of 1% polyvinyl formal) was dripped to the tail of the sample, and transmission electron microscopy observation could be directly performed after the fixing solution was completely solidified.

[0023] The universal liquid unit based on nano-quartz glass tube prepared by the above method also belongs to the protection scope of the present invention.

[0024] Another object of the present invention is to provide a novel transmission electron microscope liquid sample cell based on a quartz glass tube.

[0025] The novel transmission electron microscope liquid sample cell based on quartz glass tube provided by the present invention comprises the above-mentioned universal liquid unit based on nano-quartz glass tube.

[0026] Another object of the present invention is to provide a transmission electron microscopic observation method for liquid samples based on nano-quartz glass tubes.

[0027] The method for transmission electron microscopic observation of liquid samples based on nano-quartz glass tubes provided by the present invention utilizes the above-prepared universal liquid unit based on nano-quartz glass tubes or the novel transmission electron microscope liquid sample cell based on quartz glass tubes to directly perform transmission electron microscopic observation.

[0028] The acceleration voltage of transmission electron microscope imaging in the above method is 80-300 kV, preferably 200 kV.

[0029] Thanks to the surface effect of the inner wall of the quartz glass tube and the conical structure of the tip, for liquid samples with water and non-aqueous solvents, in the high vacuum environment of the transmission electron microscope sample chamber, even if the nanometer-scale opening of the front tip is not closed, the solvent evaporation rate is still very small, which can provide sufficient observation time. Under the standard imaging electron metering rate, 10-50e- / (A2·s), the imaging time is usually 10-30 minutes. Considering that the electron beam interacts with the sample to generate heat and accumulate charges, for liquids, especially non-aqueous solvents, after the storage unit is prepared, a carbon layer with a thickness of about 10nm can be evaporated on the surface of the glass tube by vacuum evaporation. This can effectively dissipate the accumulation of charge and local heat without affecting the imaging contrast, reduce the radiation damage of the electron beam to the sample, and further extend the imaging time.

[0030] Nano-scale quartz glass tubes have been widely used in analytical chemistry. They can be quickly prepared from low-cost quartz glass tubes through program-controlled laser drawing. The tip aperture and angle can be adjusted by adjusting the drawing parameters. There are two types: single-channel and double-channel. The thickness of the quartz tip is 10-300nm, allowing the electron beam to pass through for imaging. In addition, the quartz glass material also has good wettability and mechanical strength, ensuring its safety as a liquid storage unit under high vacuum conditions. For samples with non-aqueous solvents, after the liquid storage unit is prepared, a carbon film with a thickness of about 10nm is evaporated on the grid loaded with the glass tube using a vacuum evaporation method. The carbon film has the function of protecting the glass tube and inhibiting solvent volatilization. In addition, the carbon film coated on the surface of the universal grid can ensure that the structure of the nano-glass tube is not destroyed at a higher electron dose rate. The use of nano-scale quartz glass tubes encapsulated on a carbon film-covered grid as liquid storage units has the advantages of low cost, quick and easy preparation, fixed volume, high mechanical strength, and a wide range of observable liquid fields. It also has a contrast similar to that of silicon nitride thin film liquid chips, and is a new method for transmission electron microscopy observation of liquid samples with broad application prospects. In addition, the surface modifiable characteristics, gradient-restricted spatial structure, and controllable opening size of the quartz glass tube can play a unique role in studying the flow properties and gas-liquid properties of nano-confined fluids. The nano-openings of the quartz glass tube are also conducive to the real-time removal of gas generated by electron radiolysis in the liquid storage unit, maintaining the pressure balance in the liquid storage unit, and will not cause problems such as expansion and deformation of the liquid pool during imaging, such as silicon nitride pools.

[0031] The present invention develops a method for preparing a nano-quartz glass tube liquid storage micro-unit that is compatible with a standard transmission electron microscope sample rod, which can realize transmission electron microscopic in-situ and dynamic observation of liquid samples such as nanomaterials, soft matter (vesicles, micelles, etc.) in a liquid environment under high vacuum conditions.

[0032] Compared with the prior art, the present invention has the following beneficial technical effects:

[0033] The sample pool prepared by the present invention is compared with the existing silicon nitride and graphene pools: the sample pool of the present invention can study the objects that can be studied by both, and has similar spatial resolution; compared with a silicon nitride pool of more than 1,000 yuan, the liquid micro-unit based on glass nanotubes is only 10-30 yuan, and the silicon nitride pool requires a special electron microscope instrument, while the technology we have developed can be used with an ordinary electron microscope; compared with the low probability of a graphene pool completely encapsulating the solution and the large amount of time (>10 minutes) required to find it under an electron microscope, the technology of the present invention can be completed within minutes, thereby improving work efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 A schematic flow chart of the liquid transmission electron microscopy observation method based on nanoglass tubes provided by the present invention.

[0035] Figure 2 The following are micrographs of the prepared universal liquid storage unit and its transmission electron micrograph.

[0036] Figure 3 (A) Transmission electron microscopy image of a nano-quartz glass tube in the absence of liquid.

[0037] Figure 3 (B) is a transmission electron microscopy image of a nano-quartz glass tube in the presence of liquid.

[0038] Figure 3 (C) is a transmission electron microscopy image of a nano-quartz glass tube in the presence of liquid and bubbles.

[0039] Figure 4 (A) is an energy dispersive X-ray spectrum of the liquid storage unit containing the in-situ growth precursor solution of platinum nanoparticles in Example 1 (a solution containing 3.3 g / ml platinum acetylacetonate in o-dichlorobenzene: oleylamine (volume ratio of 29:1)).

[0040] Figure 4 (B) is a distribution diagram of the four elements of chlorine, silicon, platinum and oxygen in the liquid storage unit containing the precursor solution for in-situ growth of platinum nanoparticles in Example 1.

[0041] Figure 5This is an image of the dynamic process of platinum nanoparticle growth captured by using a nano-quartz glass tube as a liquid storage unit in Example 1. The scale bar in the figure is 20 nm in length.

[0042] Figure 6 (A) is a dynamic process image of gold nanoparticle etching captured using a nano-quartz glass tube as a liquid storage unit in Example 2.

[0043] Figure 6 (B) Figure 6 (A) shows the morphology profiles of the three nanoparticles (NP1, NP2, NP3) changing with time.

[0044] Figure 6 (C) Figure 6 (A) shows the cross-sectional area of ​​the three nanoparticles (NP1, NP2, NP3) as a function of time.

[0045] Figure 7 (A) is a liposome morphology image obtained in Example 3 using a nano-quartz glass tube as a liquid storage unit.

[0046] Figure 7 (B) Figure 7 (A) Magnified image of the liposomes labeled in Figure 2.

[0047] Figure 8 (A) is a transmission electron microscopic image of the movement of the complex formed by iron ions and thiocyanate in the two channels after solution blending occurs in the dual-channel nano-quartz glass tube in Example 4.

[0048] Figure 8 (B) is the sulfur element distribution diagram of the energy dispersive X-ray spectrum after the solutions in the two channels are mixed in Example 4. DETAILED DESCRIPTION

[0049] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. The methods described are conventional methods unless otherwise specified. The raw materials described can be obtained from public commercial channels unless otherwise specified.

[0050] Example 1

[0051] (1) Preparation of a quartz glass tube with a nanoscale tip: A P-2000 laser programmable horizontal puller (Sutter Instrument Co., USA) was used for pulling. The quartz glass tube model was QF100-70-10 (inner diameter 0.7 mm, outer diameter 1.0 mm, length 10 cm, with a drainage core). The drawing parameters were shown in Table 1. The laser heating time range was 3.40 s to 3.60 s.

[0052] Table 1 Process parameters for drawing nano-quartz glass tubes

[0053]

[0054] (2) Sample loading and liquid storage unit preparation: The precursor solution (3.3 g / ml platinum acetylacetonate in o-dichlorobenzene: oleylamine (volume ratio of 29:1) solution) used to observe the in situ nucleation and growth process of platinum nanoparticles was injected into the tube from the back. After removing the bubbles, the tube was allowed to stand for 5 minutes to allow the liquid to fill the tip. Apply a small amount of high vacuum silicone grease to about 2 mm from the tip of the nano-quartz glass tube, then cut it off with micro scissors. Under microscope observation, use an auxiliary capillary (micrometer-level glass capillary) to transfer the high vacuum silicone grease and the tip liquid unit to the carrier grid, ensuring that the needle tip and the carrier grid are basically at the same level. Finally, add about 1 μL of the fixing liquid (1,2-dichloroethane solution with a mass fraction of 1% polyvinyl formal) to the tail of the liquid storage unit. After the fixing liquid is completely solidified, use the Q150T ES plus high vacuum coating instrument (Quorum Technologies Co., UK) to evaporate a carbon layer of about 10 nm thick on the outer wall of the liquid storage unit, and then perform transmission electron microscopy observation. The prepared liquid storage unit is as follows: Figure 2 shown.

[0055] (3) Transmission electron microscopy imaging and energy spectrum acquisition: The grid containing the liquid storage unit prepared in (2) above was placed on a conventional sample rod, and transmission electron microscopy imaging was performed at an accelerating voltage of 200 kV using a field emission transmission electron microscope-FEI Tecnai F20 (Gatan OneviewIS camera, 4096×4096 pixels) to fully record the dynamic changes of the solution sample and the in-situ growth process of platinum nanoparticles. Energy dispersive X-ray spectra and element distribution images were collected by an Oxford X-MaxN TSR spectrometer, such as Figure 3 (A) As shown Figure 4 As shown in the figure, the results show that the platinum-containing precursor solution is successfully encapsulated into the nano-quartz glass tube, and the distribution of chlorine, silicon, platinum, and oxygen elements is as follows Figure 4 As shown in (B), the platinum-containing solution encapsulated in the quartz glass tube channel is continuous and full. The in-situ reduction of platinum acetylacetonate and the growth process of platinum nanoparticles are shown in Figure 5 As shown, the sampling interval of each frame is 2 seconds. Two different modes of platinum nanoparticle growth in solution can be clearly distinguished: monomer addition growth and particle fusion growth.

[0056] Example 2

[0057] (1) Preparation of a quartz glass tube with a nanoscale tip: The preparation method is the same as (1) in Example 1.

[0058] (2) Sample loading and liquid storage unit preparation: The gold nanoparticle sample (average particle size 10 nm, dilution factor 10) for observation was injected into the nanoquartz glass tube from the back of the tube. After removing the bubbles, the tube was left to stand to allow the liquid to fill the tip. A small amount of high vacuum silicone grease was applied to the tip of the nanoquartz glass tube at about 2 mm. Then, it was cut off with micro scissors. Under microscope observation, an auxiliary capillary (a micron-grade glass capillary will suffice) was used to transfer the high vacuum silicone grease and the tip liquid unit to the grid, ensuring that the needle tip and the grid were basically at the same level. Finally, about 1 μL of the fixing solution (a 1,2-dichloroethane solution of 1% by mass of polyvinyl formal) was dripped onto the tail of the liquid storage unit. After the fixing solution was completely solidified, transmission electron microscopy observation could be performed.

[0059] (3) Transmission electron microscopy: The grid containing the liquid storage unit prepared in (2) above was placed on a conventional sample holder and a field emission transmission electron microscope - FEI Tecnai F20 (Gatan OneviewIS camera, 4096 × 4096 pixels) was used to perform transmission electron microscopy at an accelerating voltage of 200 kV. Figure 6 As shown in (A), Figure 6 (B) and (C) are the morphology profile change diagram and cross-sectional area change diagram of the three nanoparticles (NP1, NP2, NP3) marked in Figure (A) during the etching process, respectively.

[0060] Example 3

[0061] (1) Preparation of a quartz glass tube with a nanoscale tip: The preparation method is the same as (1) in Example 1.

[0062] (2) Sample loading and liquid storage unit preparation: The liposome sample to be observed (lecithin: cholesterol molar ratio of 5:3, lecithin concentration of 1.5 mg / ml, dynamic light scattering average particle size of 30 nm) was injected into the nano-quartz glass tube. After removing the bubbles and letting it stand to allow the liquid to fill the tip, a small amount of high vacuum silicone grease was applied to the tip of the nano-quartz glass tube about 2 mm. It was then cut off with micro scissors. Under microscope observation, an auxiliary capillary (a micron-grade glass capillary will do) was used to transfer the high vacuum silicone grease and the tip liquid unit to the grid, ensuring that the needle tip and the grid were basically at the same level. Finally, about 1 μL of the fixative (a 1,2-dichloroethane solution of 1% polyvinyl formal) was dripped onto the tail of the liquid storage unit. After the fixative was completely solidified, transmission electron microscopy observation could be performed.

[0063] (3) Transmission electron microscopy: The grid containing the liquid storage unit prepared in (2) above was placed on a conventional sample rod and transmission electron microscopy was performed using a field emission transmission electron microscope - FEI Tecnai F20 (Gatan OneviewIS camera, 4096×4096 pixels) at an accelerating voltage of 200 kV. Figure 7 (A) is the morphology image of liposomes in solution environment. Figure 7 (B) Figure 7 (A) A local magnified image of a liposome with clear structural information selected and in focus, showing its vesicle structure.

[0064] Example 4

[0065] (1) Preparation of a double-channel quartz glass tube with a nanoscale tip: A P-2000 laser programmable horizontal puller (Sutter Instrument Co., USA) was used for pulling. The double-channel quartz glass tube model was QT120-90-7.5 (inner diameter 0.9 mm, outer diameter 1.2 mm, length 7.5 cm, with a drainage core). The drawing parameters were shown in Table 2. The laser heating time ranged from 3.90 s to 4.00 s.

[0066] Table 2 Process parameters for drawing double-channel nano-quartz glass tubes

[0067]

[0068] (2) Sample loading and liquid storage unit preparation: Inject ferric chloride solution (10mmol / L) into one channel of the dual-channel nanoglass tube, and inject potassium thiocyanate solution (60mmol / L) into the other channel. After removing bubbles and letting the liquid fill the tip, apply a small amount of high vacuum silicone grease to about 2mm from the tip of the dual-channel nanoquartz glass tube, then cut it off with micro scissors. Under microscope observation, use an auxiliary capillary (micrometer-level glass capillary) to transfer the high vacuum silicone grease and the tip liquid unit to the grid, ensuring that the needle tip and the grid are basically at the same horizontal plane, and adjust the middle partition of the dual-channel nanoglass tube to be perpendicular to the grid plane. Finally, add about 1μL of the fixing liquid (1% polyvinyl formal in 1,2-dichloroethane solution) to the tail of the liquid storage unit, and wait for the fixing liquid to completely solidify before performing transmission electron microscopy observation.

[0069] (3) Transmission electron microscopy imaging and energy spectrum acquisition: The carrier grid containing the liquid storage unit prepared in (2) above was placed on a conventional sample holder, and transmission electron microscopy imaging was performed using a field emission transmission electron microscope-FEI Tecnai F20 (Gatan OneviewIS camera, 4096×4096 pixels) at an accelerating voltage of 200 kV. The energy dispersive X-ray spectrum and element distribution images were collected by an Oxford X-MaxN TSR spectrometer. Figure 8 As shown in (A), the complex generated after the solutions in the two channels are mixed through the tip gradually moves to the rear end, indicating that the solution mixing occurs continuously in the two channels. Figure 8 (B) is the distribution diagram of sulfur elements in the dual-channel nanoglass tube. It can be seen that both channels are filled with sulfur elements, indicating that the potassium thiocyanate solution has entered the other channel, once again confirming that the solutions in the two channels have been mixed.

[0070] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A method for preparing a universal liquid unit based on a nano-quartz glass tube, comprising the following steps: 1) preparing a quartz glass tube with a nanoscale tip; 2) pouring the liquid sample to be observed into the quartz glass tube with the nanoscale tip, and letting it stand to fill the tip; 3) cutting the tip portion of the quartz glass tube with a nanometer-scale tip in the presence of a sealing reagent, transferring and loading it onto a universal grid; 4) Add a fixing solution to the tail of the sample and wait for the fixing solution to completely solidify to obtain a universal liquid unit based on the nano-quartz glass tube.

2. The preparation method according to claim 1, characterized in that: In the step 1), the length of the nanoscale tip segment of the quartz glass tube with a nanoscale tip is 0.5 mm to 2.5 mm, preferably 2 mm; Or, the radius of the nanoscale tip of the quartz glass tube with a nanoscale tip is 10-100 nm, preferably 50 nm and below, and more preferably below 10 nm.

3. The preparation method according to claim 1 or 2, characterized in that: In the step 1), the quartz glass tube with nanometer-scale tip includes two types: single-channel and double-channel; Or, in the step 1), in the method step 1), a quartz glass tube with a nanoscale tip is prepared by a program-controlled laser drawing method.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step 2), the original environment of the sample is liquid, including precursor solution, hard material, and soft material; the solvent of the liquid is water or non-aqueous solvent.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The specific method of step 3) is: using micro scissors covered with high vacuum silicone grease to cut the nanometer-scale tip of the quartz glass tube and seal its rear end in situ, and then using a capillary to assist in transferring the high vacuum silicone grease and the quartz glass tube tip with the tail embedded therein to a universal carrier grid; When the nano-quartz glass tube is a double-channel type, it is also necessary to adjust the middle partition of the double-channel nano-glass tube to be perpendicular to the grid plane.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In the step 4), the fixing liquid is a 1,2-dichloroethane solution with a mass fraction of 1% polyvinyl formal; the amount of the fixing liquid used is about 1 μL.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The method further comprises the following steps: a carbon layer with a thickness of 5-15 nm is deposited on the surface of the glass tube of the universal liquid unit based on the nano-quartz glass tube by vacuum evaporation; the thickness of the carbon layer is preferably 10 nm.

8. A universal liquid unit based on a nano-quartz glass tube prepared according to the method of any one of claims 1 to 7.

9. A novel transmission electron microscope liquid sample cell based on a quartz glass tube, comprising the universal liquid unit based on a nano-quartz glass tube according to claim 8.

10. A method for transmission electron microscopic observation of a liquid sample based on a nano-quartz glass tube, which directly performs transmission electron microscopic observation by using the universal liquid unit based on a nano-quartz glass tube as claimed in claim 8 or the novel transmission electron microscope liquid sample cell based on a quartz glass tube as claimed in claim 9; Preferably, the transmission electron microscope imaging acceleration voltage is 80-300 kV, more preferably 200 kV.